Are the Indian Stock Market and REITs integrated or segmented? An empirical study of Listed Real Estate Investment Trusts (REITs) in India - Kudtarkar, Sandeep Ganpat; Jesudasan, Smita (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
Real Estate Investment Trusts (REITs) provide investors with an indirect means of investing in income-producing real estate assets, such as office complexes, shopping plazas, hotels, and apartment buildings, by purchasing shares of publicly traded REITs. India’s first REIT, the Embassy Office Parks REIT, was listed in March 2019. This paper investigates the long-run and short-run relationships between Indian REITs and the broader equity market, as well as the listed realty stock market, examining whether these markets are integrated or segmented, and whether Indian REITs qualify as an alternative asset class within a multi-asset portfolio. The study finds a causal relationship but no cointegration, indicating the absence of a long-run relationship between Indian REITs and the equity market. This suggests the existence of segmentation between the stock market and REITs, implying that REITs can serve as a diversification tool within an investment portfolio. The paper concludes that REITs offer a diversification opportunity, with returns that, while lower than stocks due to dividend obligations, resemble those of bonds, highlighting their hybrid nature. This study contributes to the literature on alternative investments in emerging markets and provides insights for policymakers and market participants. The findings underscore the potential benefits of long-term diversification for investors who hold both real estate stocks and REITs simultaneously, making the identification of such relationships crucial for both investors and policymakers.